(untitled) (Delta Medical College Journal, 2025)
Background: Cardiovascular diseases (CVDs), one of the non-communicable diseases, has become a major public health problem in many developing countries and myocardial infarction (MI) is the number one cause of death globally. Objective: To assess the prevalence of risk factors of MI among the admitted MI patients of Combined Military Hospital (CMH), Dhaka, Bangladesh. Materials and method: This cross-sectional observational study was conducted from July to December 2012 among 104 MI patients admitted in CMH, Dhaka, Bangladesh. Data were collected through face-to-face interview using a pretested semi-structured questionnaire. Results: Majority of the respondents (61.5%) were smoker and almost all of them used to do physical exercise in terms of mild, moderate and severe forms; 26.0%, 54.8% and 19.2% respectively. About 62.5% had a history of taking extra salt with food and 16.34% were obese in terms of body mass index (BMI). Almost all of them had several chronic diseases like hypertension, diabetes mellitus (DM), chronic obstructive airway disease (COPD) and bronchial asthma. Association between smoking habit with age group revealed statistically significant relation (p<0.05). It was also revealed that BMI and monthly income was statistically significant (p<0.05). Conclusion: In this study preventable risk factors were associated with MI. Appropriate preventive measures should be taken by the competent authority to control the preventable risk factors of MI. Delta Med Col J. Jul 2022;10(2): 72-76